2014
DOI: 10.1097/qad.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

HIV protease inhibitor exposure predicts cerebral small vessel disease

Abstract: Objective HIV-associated neurocognitive disorders (HAND) remain prevalent in patients who receive highly active antiretroviral therapy (HAART) and may be associated with cumulative exposure to antiretroviral medications and other factors. We proposed that chronic toxic effects of antiretroviral drugs could contribute to cerebral small vessel disease (CSVD), which might be one of the key underpinnings of HAND. Design Clinicopathological cross-sectional study of HIV-infected adults in the California NeuroAIDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 56 publications
0
57
1
Order By: Relevance
“…43 Volumetric reductions are correlated to the frequency of white matter lesions thought to be due to SVID in HIV-uninfected study groups, providing another underlying factor that may be disproportionately present in the setting of HIV. 34,42 Our findings in both grey and white matter suggest SVID alone is insufficient to explain our findings.…”
Section: Discussionmentioning
confidence: 96%
“…43 Volumetric reductions are correlated to the frequency of white matter lesions thought to be due to SVID in HIV-uninfected study groups, providing another underlying factor that may be disproportionately present in the setting of HIV. 34,42 Our findings in both grey and white matter suggest SVID alone is insufficient to explain our findings.…”
Section: Discussionmentioning
confidence: 96%
“…Second, cortical deficits can develop in HAND patients, with executive function and learning ability being the most frequently affected domains [4749]. The development of vascular cognitive impairment also poses a substantial concern, but the evidence for this is preliminary and largely obtained from neuroimaging studies [5052]. Third, HAND can be associated with extrapyramidal features that overlap with PD [53, 54].…”
Section: Hand In the Era Of Cartmentioning
confidence: 99%
“…Recently it was demonstrated that mild and moderate/severe small vessel diseases were associated with protease inhibitor-based HAART exposure and that HAND was associated with mild CSVD (after adjusting for vessel mineralization, HIV encephalitis, microglial nodular lesions, white matter lesions, or older age). [197] Further to this potentially relevant effect on cerebrovascular disease, PI-based combination treatment has been associated with reduced amyloid phagocytosis and increased neuronal accumulation justifying some of the shared and clinical features with Alzheimer's dementia. [198,199] Efavirenz effects in the CNS are well-characterized (abnormal dreams, dizziness) and associated with higher plasma concentrations and to single nucleotide polymorphisms in genes encoding for proteins involved in the drug metabolism or transport.…”
Section: Arv Toxicity In the Cnsmentioning
confidence: 99%